'Walking between worlds': the experiences of New Zealand Māori cross-cultural adoptees. (March 2015) - Haenga-Collins, Maria; Gibbs, Anita
In New Zealand between 1955 and 1985 over 45, 000 closed stranger adoptions took place. The Adoption Act 1955 promoted the closed adoption of many Indigenous Māori children into Pākehā (white European) families. Such adoptions severed the ancestral, familial and cultural connections for thousands of Māori children. Although the Adoption Act 1955 is still the current legislation in place in New Zealand, the late 1970s saw open adoption become accepted best practice. Yet it was not until 1985, with the passing of the Adult Adoption Information Act, that adult adoptees gained access to their original birth certificate that provided their birth name and the name of their birth mother. For Māori adoptees this offered a chance to search for their birth parents. It also offered the possibility to trace the previously unknown knowledge of their tribal affiliations and Māori cultural heritage. This article explores the narratives of six Māori adults who were adopted into white families. Using a Māori-centred research approach, it found that Māori adoptees often struggled with their dual identities, feeling they were always 'walking between worlds', never fully belonging in either their birth or adoptive families, or fitting comfortably with either a Māori or Pākehā cultural identity.